Influenza-associated Neurologic Complications in Hospitalized Pediatric Patients: A Multicenter Retrospective Study in Republic of Korea. Issue 12 (7th September 2021) - Choi, Gwang-Jun; Park, Ji Young; Choi, Joon-Sik; Choi, Sae Rom; Kim, Dongsub; Lee, Jun Hwa; Woo, Young-Jong; Lee, Jeehun; Kim, Yae-Jean
Abstract : Background: The rates of influenza-associated neurologic complications are variable among studies, and a difference has been observed between the Western and Asian countries. The study aims to evaluate the frequency and characteristics of influenza-associated neurologic complications. Methods: We performed a retrospective review of hospitalized cases of influenza infection from October 2010 to April 2017 from 3 referral hospitals. Results: A total of 1988 influenza cases were identified. Influenza-associated neurologic complications were 161 cases (8.1%); influenza virus A was detected in 113 (70.2%) cases, B in 47 (29.2%) cases and both A and B in 1 case (0.6%). Twenty-four patients (15%) had underlying neurologic diseases. The most common diagnosis was a simple febrile convulsion (44%), followed by complex febrile convulsion (29%), fever-provoked seizure under pre-existing neurologic disease or afebrile seizure (14%), encephalopathy/encephalitis (8%) and meningitis (5%). Most of the patients fully recovered (96%). Three patients (1.9%) died of myocarditis (n = 1), encephalopathy (n = 1), and simultaneous encephalitis and myocarditis (n = 1). Pre-existing neurologic disease, age groups of 6 months to 6 years and 6–12 years were a risk factor of influenza-associated neurologic complications with an adjusted odds ratio of 5.41 (95% confidence interval [CI] 3.23–9.06, P < 0.001), 12.99 (95% CI 1.77–95.19, P = 0.01) and 8.54 (95% CI 1.14–64.79, P = 0.04), respectively. There was no association between neuropsychiatric adverse events and oseltamivir prescription ( P = 0.17). Conclusions: Influenza-associated neurologic complications are not uncommon, and most patients fully recovered. The frequency of influenza-associated neurologic complications in Korean children was not significantly different from that of children in Western countries.